Australian Early Childhood Educators: From Government Policy to University Practice - Davies, Sharon; Trinidad, Sue (Taylor and Francis, 2013)
This article provides an overview of the Australian Federal Government initiatives in the area of early childhood with regard to the provision of early childhood education and care. These changes have influenced a Western Australian university to develop an innovative birth to 8 years preservice educator education curriculum. Using an ecological approach, this preservice curriculum reform is designed to address the growing need for teachers who recognize the importance of a child’s physical, emotional, and cognitive development from birth to 8 years as significant in preparing young children for entry into “formal learning.”